The COVID-19 impact on corporate leverage and financial fragility - Haque, Sharjil Muktafi,Varghese, Richard (International Monetary Fund, 2021)
We study the impact of the COVID-19 recession on capital structure of publicly listed U.S. firms. Our estimates suggest leverage (Net Debt/Asset) decreased by 5.3 percentage points from the pre-shock mean of 19.6 percent, while debt maturity increased moderately. This de-leveraging effect is stronger for firms exposed to significant rollover risk, while firms whose businesses were most vulnerable to social distancing did not reduce leverage. We rationalize our evidence through a structural model of firm value that shows lower expected growth rate and higher volatility of cash flows following COVID-19 reduced optimal levels of corporate leverage. Model-implied optimal leverage indicates firms which did not de-lever became over-leveraged. We find default probability deteriorates most in large, over-leveraged firms and those that were stressed pre-COVID. Additional stress tests predict value of these firms will be less than one standard deviation away from default if cash flows decline by 20 percent
10.5089/9781589064126.001
Keywords: Graue Literatur; Corporate Debt; Optimal Capital Structure; Rollover Risk; Distance-To-Default; Default Risk; Stress Tests; Corporate Finance and Governance; Financial Economics; General Financial Markets; COVID-19; Capital and Ownership Structure; Financial Risk and Risk Management; Financing Policy; Corporate Finance; Money and Monetary Policy; Banks and Banking; Financial Economics: General; General Financial Markets: General (includes Measurement and Data); Corporate Finance and Governance: General; Financial Risk Management; Diseases: Contagious; Economics: General; Value of Firms; Goodwill; Bankruptcy; Liquidation; Health Behavior; International Financial Markets; Financial Institutions and Services: General; Monetary Systems; Standards; Regimes; Government and the Monetary System; Payment Systems; Economic & financial crises & disasters; Economics of specific sectors; Infectious & contagious diseases; Finance; Ownership & organization of enterprises; Monetary economics; Financial services law & regulation; Macroeconomics; Health; Asset valuation; Asset and liability management; Economic sectors; Currencies; Credit risk; Financial regulation and supervision; Currency crises; Informal sector; Economics; Communicable diseases; Asset-liability management; Business enterprises; Money; Financial risk management